Influence of machining cutting speed on cutting force, tool flank wear on PVD inserts by turning of Ti-6Al-4V alloy - Raghavendra, M. J.; Ramachandra, C. G.; Srinivas, T. R.; Pai, M. Prashanth (AIP conference proceedings, 2020)
Tool wear is one in all the foremost necessary issues in cutting Ti alloys thanks to the high-cutting temperature and robust adhesion. Recently, the high-speed machining method has become a subject of nice interest for Ti alloys, not solely as a result of it will increase material removal rates, however, additionally as a result of it will completely influence the properties of the finished work piece. However, the method could lead to the rise of cutting force and cutting temperature which can accelerate tool wear. In this paper, turning experiments of Ti-6Al-4V alloy were conducted at high speeds using both uncoated and coated carbide tools. The obtained results show that the cutting force will increase considerably at higher cutting speed whether or not the cutter is an uncoated inorganic compound or TiN/TiAlN physical Vapour deposition (PVD)-coated inorganic compound. For uncoated carbide tools, the mean flank temperature is almost constant at a higher cutting speed, and no obvious abrasion wear or fatigue can be observed. However, for TiN/TiAlN PVD-coated carbide tools, the mean flank temperature always increases as the increase of cutting speed, and serious abrasion wear can be observed. In conclusion, the cutting performance of uncoated inserts is comparatively higher than TiN/TiAlN PVD-coated inserts at a better cutting speed.